Airlift pump type heat transport equipment - YAMADA AKIRA; IPPOSHI SHIGETOSHI; UEHARA NOBUTETSU (2004)
可获得热阻小、热输送量大的气泡泵型热输送设备。具有热交换循环溶液存放容器(4)和循环溶液输送通道(A)；该热交换循环溶液存放容器(4)由第1空间(4a)和由连通孔(2)连通到第1空间(4a)的第2空间(4b)构成，在各空间收容热交换用循环溶液(1)和循环溶液的蒸汽(12)；循环溶液输送通道(A)具有与设于该容器(4)的溶液送出口(6)连接并设置有显热放散热交换器(10)的管(6)、设于容器(4)内的管(7)、及与气液二相流体送入口(8)连接并设置有加热热交换器(11)的管(9)。从气液二相流体送入口(8)流入的气液二相流体仅流入到第1空间(4a)，由于流入而在各空间(4a、4b)内产生压力差时，第1空间(4a)与第2空间(4b)的气液界面位置变化。 A vapor-lift pump heat transport apparatus having a small heat resistance and a large heat transport capacity. A heat exchange circulating solution container has a first space and a second space communicating with the first space through a communication opening and contains a heat exchange circulating solution, and vapor thereof, in each space. A circulating solution transport passage includes a pipe connected to the solution outlet of the container and provided with a sensible heat releasing heat exchanger, a pipe disposed in the container, and a pipe connected to a vapor-liquid two-phase fluid inlet and provided with a heating heat exchanger. A vapor-liquid two-phase fluid flows into only the first space through the vapor-liquid two-phase fluid inlet. When the entrance of the vapor-liquid two-phase fluid has caused a pressure difference between the first and second spaces, a difference occurs between the positions of the vapor-liquid interfaces in the first and second spaces.